Laicyzacja rodziny – jej przyczyny i niektóre konsekwencje - Bortkiewicz, Paweł (Społeczeństwo, 2022)
One of the most significant signs of the times (kairos) is the transformation in marriage and family. Their diagnosis was brilliantly presented by St. John Paul II in Familiaris Consortio and one can risk a thesis that this diagnosis is still valid. The Pope mentions both the light and the shadow of the modern family. Among the symptoms of the crisis, he points to the weakening of ties within the marriage community, which is associated with individualism and utilitarianism. It also leads to a distortion of the sense of human sexuality, which is subjected to hedonism. In this perspective, all relationships and manifestations of sexual orientations are allowed, as long as they serve the satisfaction of pleasure. One should also pay attention to the crisis of authority in the family and the impermanence of marriages. Among the reasons for this state of affairs, attention must first be paid to sin, which is turning away from God, clearly expressed in the phenomena of secularization. The effect of this is the detachment of freedom from truth (Truth), which can be illustrated by the revolt against life and against God, which took place in autumn of 2020 in Poland. Apart from this deepest cause of the internal crisis, there are external causes related to, among other things, the shape of the nation’s policy and the influence of media.